The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11213402
|View full text |Cite
|
Sign up to set email alerts
|

Salicornia bigelovii, S. brachiata and S. herbacea: Their Nutritional Characteristics and an Evaluation of Their Potential as Salt Substitutes

Abstract: Excessive sodium (salt) intake in our diet is a main contributor to hypertension and a major risk factor for cardiovascular illnesses. As a result, research has made great efforts to develop salt alternatives, and Salicornia spp. offers a very high potential in the food industry for its promising functional characteristics. This review focuses on the nutritional profile, health effects and commercial potential of three specific species of the Salicornia genus: S. bigelovii, S. brachiata and S. herbacea. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 112 publications
(181 reference statements)
2
9
0
Order By: Relevance
“…Salicornia extracts represent a complex source of biomolecules with neuroprotective or antioxidant activities [ 10 ]. As expected by previous reports [ 26 , 27 , 28 , 29 , 30 ], we found many different compounds that can be responsible for the therapeutic effect of S-EE, mainly including caffeoylquinic acid derivatives, flavonoids, and fatty acids. Although the exact therapeutic mechanisms of S-EE were not revealed in this study, several phytochemicals present in the plant might have contributed to the protective effect in combination.…”
Section: Discussionsupporting
confidence: 89%
“…Salicornia extracts represent a complex source of biomolecules with neuroprotective or antioxidant activities [ 10 ]. As expected by previous reports [ 26 , 27 , 28 , 29 , 30 ], we found many different compounds that can be responsible for the therapeutic effect of S-EE, mainly including caffeoylquinic acid derivatives, flavonoids, and fatty acids. Although the exact therapeutic mechanisms of S-EE were not revealed in this study, several phytochemicals present in the plant might have contributed to the protective effect in combination.…”
Section: Discussionsupporting
confidence: 89%
“…ABTS scavenging capacity of SADE is similar to that of S. europea originating from Italy (ABTS = 15.1 mg TE/g) reported by Costa et al [ 49 ]. Halophyte plant extracts are characterized by promising in vitro antioxidant activities, as reported by many authors [ 19 , 22 , 50 ]. Phenolic acids such as ferulic acid, cinnamic acid, chlorogenic acid and coumaric acid were reported as the main phenolic compounds in many halophytes [ 18 , 37 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 88%
“…Salicornia genus has recently been commercialized in Europe and Asia as a staple food, and it is used in green salads for its saltiness [ 20 ] or as an ingredient in various recipes as tea powder, seasoned vegetable, makgeolli, pickled vegetables, vinegar and fermented food [ 21 ]. Various promoting therapeutic applications have been reported for Salicornia species: Salicornia herbacea and Salicornia bigelovii are in particular used against oxidative stress, inflammation gastroenteritis, cancer, diabetes, asthma and hepatitis [ 21 ] and in the treatment of various diseases such as obesity, hyperglycemia and hyperlipidemia [ 22 , 23 ]. Salicornia herbacea supplementation reduces fat accumulation in the liver and regulates hepatic triglycerides [ 24 ], decreases lead-induced oxidative stress, and exerts cytoprotective action [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is consumed as a common vegetable or as a medicinal herb. Research has demonstrated that as a seasonal sea vegetable, S. bigelovii possesses a curious, salty, and crisp taste and is rich in protein, various trace elements, cellulose, vitamins, and essential amino acids [ 2 ]. Therefore, S. bigelovii could be consumed as a green organic vegetable.…”
Section: Introductionmentioning
confidence: 99%